Personalized Stem Length Optimization in Hip Replacement: A Microscopic Perspective on Bone—Implant Interaction - Su Min Kim; Jun Won Choi; Jung Jin Kim (Bioengineering, 2024)
Total hip replacement (THR) surgery involves the removal of necrotic tissue and the replacement of the natural joint with an artificial hip joint. The demand for THR is increasing due to population aging and prolonged life expectancies. However, the uniform length and shape of artificial hip joints can cause stress shielding, leading to implant loosening and femoral fractures. These issues arise because these designs fail to account for the unique anatomical and biomechanical characteristics of individual patients. Therefore, this study proposes and validates a method to optimize stem length by considering bone microstructure and daily load. The results demonstrated that the optimal stem length varies with loading conditions and significantly reduces stress in the cortical bone while maintaining an appropriate strain energy in the cancellous bone, thereby preventing bone loss. These findings underscore the importance of patient-specific stem design for improving implant stability and clinical outcomes.